HUBUNGAN PENAMBAHAN BERAT BADAN IBU SELAMA KEHAMILAN DENGAN BERAT BADAN BAYI BARU LAHIR DI RSI IBNU SINA BUKITTINGGI TAHUN 2014 - Amelia, Rini (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
The low nutrient intake and nutritional status of pregnant women during pregnancy can lead to a variety of impacts for both the mother and the baby. One is born with low birth weight (LBW), ie birth weight below 2500 grams. The goal here is to determine the mother's weight gain during pregnancy weight newbornbaby. This type of research is analytic survey with retrospective study design with the entire population of mothers delivered at Ibnu Sina RSI Bukittinggi. The sampling method is accidental sampling with a sample of how that is at least 30. The data are collected through a checklist sheet. Data processed by the computerized analysis of univariate and bivariate analysis. The results showed no significant association between maternal weight gain during weight newborns (p = 0.001). From these results it can be concluded maternal weight gain during pregnancy affects the weight newborns. Results of the study found a high rate of maternal LBW less attention because nutrients. Researchers expect all pregnant women should be adequate nutrition during pregnancy and particularly health workers to monitor maternal weight gain during pregnancy